Leptomeningeal collateral vessels are a major risk factor for intracranial hemorrhage after carotid stenting in patients with carotid atherosclerotic plaque. (3rd April 2015) - Lee, Kang Ji; Kwak, Hyo Sung; Chung, Gyung Ho; Song, Ji Soo; Hwang, Seung Bae
Abstract : Aim: To evaluate the relationship between leptomeningeal collaterals and intracranial hemorrhage (ICH) after carotid artery stenting (CAS). Methods: A retrospective study was undertaken of 228 patients (median age 75 years (range 44–90); 187 men and 41 women) who underwent CAS due to unilateral carotid atherosclerotic plaque from January 2009 to December 2013. Cerebral angiographic findings were classified into three patterns: type I, normal visualization of the anterior and middle cerebral arteries without leptomeningeal collaterals; type II, visualization of the middle cerebral artery only without leptomeningeal collaterals; and type III, visualization of leptomeningeal collateral flow. Results: For all cerebral angiographic findings, 146 (64.0%) were type I, 61 (26.8%) were type II, and 21 (9.2%) were type III. Four patients (1.8%) died with fatal ICH after CAS and had type III angiographic findings (19%). The prevalence of ICH in patients with leptomeningeal collateral vessels was significantly higher than in patients without leptomeningeal collateral vessels (19% vs 0%, p<0.0001). The percentage of carotid stenosis in patients with ICH based on North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria was significantly higher than in patients without ICH (89.8±3.6% vs 72.8±12.8%, p=0.014). Conclusions: Leptomeningeal collateral vessels are a major risk factor for ICH after CAS in patients with carotid atherosclerotic plaque.